75th anniversary of Doctor of Physical and Mathematical Sciences, Professor M.I. Ramazanov - Orumbayeva, N.T. (Bulletin of the Karaganda University. Mathematics Series, 2024)
February 24, 2024 to Doctor of Physical and Mathematical Sciences, Professor M.I. Ramazanov turned 75 years old. M.I. Ramazanov is a highly qualified specialist in the field of loaded partial differential equations, integral equations, and their applications to applied problems.